PENERAPAN METODE PETA PIKIRAN (MIND MAPPING) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV D SD NEGERI 37 PEKANBARU - Dwinda Valiandini; Eddy Noviana; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to find out whether the implementation of Mind Mapping method can improve social science learning results of class IV D students in SD Negeri 37 Pekanbaru. The type of this research is classroom action research (CAR) with the research subjects are class IV D students which amounts to 32 students. The data collection techniques used is observation and tests. The research concluded that social science learning which using mind mapping method can improve the teacher’s activity, student’s activity and social science learning result. At the first meeting of cycle I, the teacher’s activity percentage was 64% and categorized good, at the second meeting the percentage increased to be 72% and categorized good. For cycle II at the first meeting the percentage was 77% and categorized good, at the second meeting increased to be 86% and categorized very good. Then for student’s activity cycle I at the first meeting the percentage was 53% and categorized enough, in the second meeting the percentage was 58% and categorized enough. For the first meeting of cycle II the percentage was 77% and categorized good, at the second meeting the percentage was 86% and categorized very good. The student’s social science learning result from the average grades before actions (basic score) was 70,06 increased at cycle I to be 82,18 with the percentage increase by 17,30% and at cycle II the average grades increased to be 84,68 with the percentage increase by 20,18% from the basic score by 70,06.Keywords: Mind Mapping Method, learning result.